Modul Pencemaran Lingkungan Berbasis Biology Environment Technology Society untuk Matakuliah Dasar Ilmu Lingkungan - Auliyah Shofiyah; Sueb Sueb; Mimien Henie Irawati Al-Muhdhar (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to produce Environment Pollution valid and practice modul based on Biology Environment Technology Society (BETS) of the material, the validity of teaching materials, and practicality. This developmental research adopted the ADDIE development model. The result of material expert validation was 100% with a very valid category. The results of the validation of teaching material experts amounted to 99.50% with a very valid category. The results of the assessment by field practitioners amounted to 90.98% with a very practical category. The results of the assessment of usage by students amounted to 90.35% with a very practical category. Based on these results it can be concluded that the BETS-based environmental pollution module that has been produced has been appropriate to be used as teaching material for the Environmental Science Basic course.Abstrak: Penelitian ini bertujuan untuk menghasilkan modul pencemaran lingkungan berbasis BETS (Biology Environment Technology Society) yang valid dan praktis. Model pengembangan yang digunakan yaitu model pengembangan ADDIE. Hasil validasi ahli materi sebesar 100% dengan kategori sangat valid. Hasil validasi ahli bahan ajar sebesar 99,50% dengan kategori sangat valid. Hasil validasi oleh praktisi lapangan sebesar 90,98% dengan kategori sangat praktis. Hasil penilaian penggunaan oleh mahasiswa sebesar 90,35% dengan kategori sangat praktis. Kesimpulan penelitian yaitu modul pencemaran lingkungan berbasis BETS (Biology Environment Technology Society) yang dihasilkan telah layak digunakan sebagai bahan ajar untuk matakuliah Dasar Ilmu Lingkungan.